(untitled) (Journal of the College of Education for Women, 2019)
The existence of succession system has appeared in Arab Islamic state after the death of the prophet Mohammed (peace be upon God and peace), So there was caliphate, then the Umayyad dynasty in Syria , until 132 AH , the date o the emergence of the Abbasid state adopted a system ministry formally , hafs bin sulaiman ( Abu salamah Khallal ) was the first minister emerged on the political scene. He was killed at the time of the first Abbasid caliph , Abu Albbas , incest 132-136 who had put Khalid bin barmak as a minister instead of Hafs bin Sulaiman . During the reign of AL-Mansur 136-158 , there was an importance and a place for the ministry , despite of AL-Mansur strength personality that covered on his ministers personalities like Abu Ayub AL-Moryaua and later AL-Rabea Ben Younis .